PERGERAKAN INDEKS HARGA SAHAM GABUNGAN DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA - Ekayana Sangkasari Paranita; Suhaji Suhaji; Daud Johar Setyawan (Faculty of Economics and Business Diponegoro University, 2018)
The movement of Jakarta Composite Index (JCI) reflects the simultaneous performance of companies listed on the Indonesia Stock Exchange (IDX). JCI can be an investment guide because it describes the macro economic condition. This study aims to analyze the effect of inflation, exchange rate (IDR/USD) and Dow Jones Index on JCI in IDX period 2008-2016. The data comes from monthly data of inflation, exchange rate (IDR/USD), Dow Jones Index and JCI. The analysis technique used is multiple linear regression analysis. The results showed that inflation did not affect the JCI, while the Exchange Rate (IDR/USD) and Dow Jones Index had a positive effect on JCI. Inflation did not affect the JCI because in the research period, inflation was within the range below 10 percent so it did not have a significant impact on JCI. The most dominant variable influencing JCI is exchange rate (IDR/USD).